PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN LIMBAH BAGLOG JAMUR TIRAM MENJADI PUPUK ORGANIK PADA KWT JAMUR TIRAM JAWA GADUT SAIYO KOTA PADANG - Obel, Obel; S, Meisilva Erona S; Putri, Afrianingsih; Arifnur, Adi Arga; Zaqi, Fahrul; Mouza, Faiqal Ikhsan; Fiqri, Muhammad (LPPM Universitas Andalas, 2025)
Oyster mushrooms are a potential commodity to be developed because they can generate profits on both small and large scales. This is due to their high demand and selling value in both traditional markets and supermarkets. Along with this, continuous production activities produce baglog waste, which has so far only been piled up or burned. If left in this condition, it can become a new problem in oyster mushroom cultivation activities, such as becoming a source of pests and diseases that impact oyster mushroom production. Therefore, it is necessary to process baglog waste into economically valuable products such as organic fertilizer. The purpose of this community service activity is to increase the knowledge and skills of members of the Jawa Gadut Saiyo Oyster Mushroom Group (KWT) in processing baglog waste into organic fertilizer. This activity uses a participatory and applicative approach by actively involving KWT members in all stages of the activity. The activity was carried out in June 2025 using a socialization and demonstration method divided into 5 stages of activities: filling out a questionnaire, socialization, discussion, and demonstration. The results of the activity showed a very good increase in knowledge of KWT members (100%) regarding the processing of baglog waste into organic fertilizer after the socialization of baglog waste processing. Members of the Gadut Saiyo Javanese Oyster Mushroom KWT became skilled in making organic fertilizer according to the implementation stages and produced organic fertilizer that was ready for field application.